Correlation between MMP-9 Level and Diastolic Dysfunction in Concentric Left Ventricular Hypertrophy Patients - Pramudyo, Miftah; Jungjunan, Ridho; Martanto, Erwan; Achmad, Chaerul (Faculty of Medicine Universitas Padjadjaran, 2021)
Objective: To establish the relationship between plasma matrix metalloproteinase (MMP)-9 levels and diastolic functional abnormalities using the E/e’ measurement in concentric type Hypertensive Heart Disease (HHD) patients.Methods: A cross-sectional study was conducted from November 2014 to January 2015 in population with hypertension and concentric Left Ventricular Hypertrophy (LVH). Diastolic function was assessed with E/e’ measurement using echocardiography. The relationship between the two variables was analyzed using Spearman correlation.Results: Thirty-nine subjects (14 males, 35.9%) with the average relative wall thickness of 0.7(±0.15), average body weight of 63.45 (±12.97) kg, average height of 155.51 (±7.12) cm, average body mass index of 26.23 (±5.08) kg/m2, and mean age of 55 (±10) years were fit to be included in the analysis. The median systolic blood pressure was 140 (110-220) mmHg while the median diastolic blood pressure and median left ventricular mass index were 80 (70-110) mmHg and 119.24 (103.05-205.69) g/m2, respectively. The median MMP-9 was measured at 108 (4-460) ng/mL and the median E/e' was 10.99 (6.2-20.42). There was a significant positive correlation between MMP-9 and E/e' (r = 0.416, p = 0.004).Conclusion: There is a significant moderate positive correlation between the MMP-9 level and diastolic dysfunction in concentric LVH patients.